Methodology of the work based in the scientific method: opinion of nurses and academic nursing - Vall, Janaina; Silva, Sandra Honorato da (Rev Rene, 2003)
Article based in the opinion analysis of nurses and nurses academic that wording at Unit of Intensive Therapy, aiming at to compare the vision of these in relation to Nursing Attendance Systematic, nursing as a whole, change process and professional performance. It is treated of a research descriptive, where the result evidences different opinions among the involved classes.